Safety culture in the context of health organizations: an integrative review (Research, Society and Development, 2020)
This study aimed to analyze the scientific production about the safety culture in the context of health organizations. It is an integrative literature review, carried out in the databases: Scientific Electronic Library Online (SCIELO), Medical Literature Analysis and Retrieval Sistem on-line (MEDLINE), Cumulative Index to Nursing and Allied Health Literature (CINAHL). Medical Subject Headings (MESH) descriptors were used: Culture, Health; Safety; Patients; Health Sciences Organizations and Descriptors (DeCS): Culture, Health, Safety; Patients; Organizations, selecting 24 articles. Two aspects of analysis were organized: the need to strengthen the intra-organizational dimensions recognized through the team's perceptions and managerial responsibilities as facilitators for the perpetuation of the safety culture. It is concluded that studies that reveal the perceptions and practices in safety in health organizations, become fundamental and help managers and supervisory leaders to tread the paths for safe practices, benefiting employees, organizations, patients and society in general.